System Requirement in View Of Users and Process for Content Management and Academic Support System for Computer Laboratory (Case Study: Software Laboratory Center Binus University) - Win Ce; Hanny Juwitasary; Hendro Hendro (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The system for Laboratory Information will take focus on determining the need for information systems related to the management, content development and academic management in the laboratory. These processes will focus on understanding the need and system requirement for a laboratory information system that focus on content management and the way to design a process to make sure the continuation of content creation can be done. With the design of the laboratory information system is expected to serve as a sample in the development of similar application for the course in general. The methodology to be used is to use the study of literature, design, and testing of laboratory information systems.